A Comparative Study between Minimally Invasive Plate Osteosynthesis versus Open Reduction and Internal Fixation for Distal Third Tibia Fractures - Reza Zandi; Shahin Talebi; Amir Mehrvar; Shirin Sheibani; Akbar Ehsani; Saeed Nodehi (Journal of Orthopedic and Spine Trauma)
Background: Despite the array of surgical and non-surgical approaches available for treating distal tibia fractures, managing unstable fractures continues to pose a challenge. This study aims to compare the advantages and clinical outcomes of the Minimally Invasive Plate Osteosynthesis (MIPO) and Open Reduction and Internal Fixation (ORIF) in managing distal third tibia fractures.